Development and validation of an RNA sequencing panel for gene fusions in soft tissue sarcoma. Issue 5 (10th March 2022) - Hu, Wanming; Yuan, Li; Zhang, Xinke; Ni, Yang; Hong, Dongchun; Wang, Zhicai; Li, Xiaomin; Ling, Yuan; Zhang, Chao; Deng, Wanglong; Tian, Minqi; Ding, Ran; et al.
Abstract: Gene fusions are one of the most common genomic alterations in soft tissue sarcomas (STS), which contain more than 70 subtypes. In this study, a custom‐designed RNA sequencing panel including 67 genes was developed and validated to identify gene fusions in STS. In total, 92 STS samples were analyzed using the RNA panel and 95.7% (88/92) successfully passed all the quality control parameters. Fusion transcripts were detected in 60.2% (53/88) of samples, including three novel fusions ( MEG3 – PLAG1, SH3BP1 – NTRK1, and RPSAP52 – HMGA2 ). The panel demonstrated excellent analytic accuracy, with 93.9% sensitivity and 100% specificity. The intra‐assay, inter‐assay, and personnel consistencies were all 100.0% in four samples and three replicates. In addition, different variants of ESWR1 – FLI, COL1A1 – PDGFB, NAB2 – STAT6, and SS18 – SSX were also identified in the corresponding subtypes of STS. In combination with histological and molecular diagnosis, 14.8% (13/88) patients finally changed preliminary histology‐based classification. Collectively, this RNA panel developed in our study shows excellent performance on RNA from formalin‐fixed, paraffin‐embedded samples and can complement DNA‐based assay, thereby facilitating precise diagnosis and novel fusion detection. Abstract : We established and validated of a sarcoma‐tailored 67‐gene RNA panel for the improvement of STS molecular diagnosis. This panel can detect known or unknown gene fusions, thereby serving as a good supplement for DNA‐based assays. Moreover, the method is applicable to routinely processed FFPE tissue samples and bears a great potential for facilitating future integrated STS diagnostics as molecular classification.